Family correlates of child outcomes among rural Malay families - Arshat, Zarinah; Baharudin, Rozumah (Universiti Putra Malaysia Press, 2014)
The study examined the relationship between familial factors (i.e. number of children, economic strain, marital quality and parental nurturance) and child outcomes (self-esteem and academic achievement) among rural Malay families. The participants comprised 200 parents with a child aged from7 to 12 years. Findings indicated that children with higher self-esteem tended to have parents with positive parental behaviour and come from families with high economic strain. Economic strain also was found to significantly correlate with children's academic achievement. These findings imply a significant contribution of parental nurturance and economic strain on children's self-esteem and academic achievement.